Water-soluble organic nitrogen in the gas phase measured by the denuder–filter pack method. Issue 1 (1st January 2017) - Matsumoto, Kiyoshi; Yamato, Koki
Abstract: The WSON in the gas phase and aerosols were simultaneously measured by the denuder–filter pack method. Approximately 33 ± 18% of the WSON in the atmosphere existed in the gas phase. A large portion (approximately 76 ± 33%) of the gaseous WSON collected in the present sampling method was occupied by basic species. The gaseous basic and acid WSON showed about one-sixth of the nitrogen concentrations of the gaseous NH3 and HNO3, respectively. These results indicate that the gaseous WSON is also an important fixed nitrogen species in the atmosphere.